Performance Analysis of the SimInvest Application Programming Interface Using Load Testing - Cut Dahri Fajrina El Qahar; Dewi Agushinta Rahayu; Lana Sularto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study evaluates the performance capacity of the SimInvest application programming interface (API), with emphasis on stock transaction and portfolio services that are frequently accessed during peak market activity. The study used an applied performance-testing design through Apache JMeter by simulating concurrent user loads of 100, 500, 1,000, 2,000, and 4,000 users. The observed indicators were response time, transactions per second, and error rate. The findings show that the application remained usable under 100 and 500 concurrent users, with low aggregate error rates of 4.80% and 4.48%, although several history-related endpoints already showed failed requests. When the load reached 1,000 users, the total error rate increased to 53.17%, indicating a clear decline in service reliability. Under 2,000 and 4,000 users, the system recorded error rates of 49.04% and 65.32%, with repeated failures in Account Cash, Cash Withdrawal, Order List, Portfolio, RDN History, RDN Info, and Trade List services. These findings indicate that the present infrastructure requires API optimization, query tuning, server-capacity improvement, load balancing, and real-time monitoring to maintain reliable fintech services during traffic spikes.